Thanh khoản cổ phiếu khi doanh nghiệp mua lại cổ phần trên thị trường tự do - Tran Thi Hai , Ly (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
This paper examines the effect of share repurchases on stock liquidity surrounding announcement dates, and in the repurchasing year. Using hand-collected 525 repurchase announcements of Vietnamese firms during the period from 2007 to 2016, the author finds a little improvement in liquidity in short term. Controlling for some potential determinants of stock liquidity, the result shows that the effective rate of repurchase reduces stock price sensitivity, but does not affect two other aspects of liquidity, namely depth and relative spread. Therefore, the author concludes that the liquidity effect of repurchase weakly supports the competing market-maker hypothesis.
Keywords: Share repurchase; Stock liquidity